Integrasi-Interkoneksi: Pengembangan Pendidikan Islam di Perguruan Tinggi Keagamaan - Badrus Syamsi; Khojir Khojir (JIE (Journal of Islamic Education), 2023)
The dichotomy of science is still attached to Indonesian society, especially Muslims. For this reason, Islamic Religious Higher Education exists to unravel and bring together science and religion in the academic space. The purpose of this paper is an offer in the development of Islamic education in Islamic Higher Education. The study in this paper uses library research and content analysis methods as analytical methods. The results of this study offer various constructions that are produced in bringing together science and religion with an integration-interconnection approach. The encounter between science and religion will provide a strong foundation for scholarship by paying attention to various aspects in the realm of theology and humanity.